PENGARUH CAPITAL ADEQUACY RATIO (CAR) DAN QUICK RATIO (QR) TERHADAP RETURN ON ASSETS (ROA) PADA BANK UMUM SYARIAH DI INDONESIA2011-2013 - Kamalia Sani, Kamalia Sani Kamalia Sani (I-Economics, 2015)
The aim of this research is to determine the influence of the Capital Adequacy Ratio (CAR) and the Quick Ratio (QR) on Return On Assets (ROA) of the bank financial performance.Data used in this study is secondary data in the form of financial statements of Islamic Banks in Indonesia 2011-2013. Data source for this study were obtained through quarterly report. This study took 6 samples of Islamic Banks in Indonesia, which consists of 2 foreign exchange banks and 4 non-foreign exchange banks with a sampling technique based on purposive sampling.The data during study period shows a normal distribution.Using multiple linear regression, the research finds out that 17.6% ROA can be explained by the independent variables CAR and QR. While 82.4% is explained by other causes beyond the study model which is the contribution of the other independent variables besides the two variables in this study. Key Words: Capital Adequacy Ratio (CAR) Quick Ratio (QR) Return On Assets (ROA) and Bank Performance